Revised classification and evolution of leucotrichiine microcaddisflies (Trichoptera: Hydroptilidae) based on morphological and molecular data. (5th February 2016) - SANTOS, ALLAN P. M.; NESSIMIAN, JORGE L.; TAKIYA, DANIELA M.
Abstract: Hydroptilidae constitute the most diverse caddisfly family, with over 2000 species known from every habitable continent. Leucotrichiinae are exclusively New World microcaddisflies, currently including over 200 species and 17 genera. Phylogenetic analyses of Leucotrichiinae relationships based on 114 morphological characters and 2451 molecular characters from DNA sequences were conducted. DNA sequences analysed were from one mitochondrial gene, cytochrome oxidase I (653 bp), and four nuclear genes, carbamoylphosphate synthase (802 bp), elongation factor 1α (352 bp), histone 3 (308 bp) and 28S rDNA (336 bp). The morphological matrix included 94 taxa (with representatives of all included genera) and the molecular matrix included 62 taxa. Individual and combined datasets were analysed under parsimony and Bayesian inference. In addition, a relaxed molecular clock divergence time estimate was conducted to determine the age of the subfamily and major lineages. All Bayesian inference analyses strongly suggest a monophyletic Leucotrichiinae, which initially diverged at approximately 124 Ma into two monophyletic groups of genera. These groups are herein elevated to tribal status, Alisotrichiinitrib.n. and Leucotrichiini Flintsensu n. Several genera of Leucotrichiini were not recovered as monophyletic clades and some nomenclatural changes are proposed to reflect their phylogenetic history. These include the synonymy of Abtrichia with Peltopsyche ; transfer of Betrichia hamulifera to Costatrichia ; transfer of Betrichia alibrachia and Costatrichia falsa to Leucotrichia ; and transfer of Costatrichia fluminensis to Acostatrichia . Additionally, Tupiniquintrichia gen.n. is described to include Peltopsyche maclachlani and Leucotrichia procera . According to our results, crown diversifications of both Alisotrichiinitrib.n. (∼80 Ma) and Leucotrichiinisensu n. (∼103 Ma) occurred after complete separation of South America from Africa. Current distributions of most leucotrichiine genera are probably a result of migration from South America towards the north using the proto‐Caribbean archipelago (100 to 49 Ma). This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:FB6A3385-323D-41AF-B4BE-E19A393A493C .